Stan wielogatunkowego lasu naturalnego (Abies, Fagus, Picea) regla dolnego w rezerwacie Oszast na tle stanu monokultur świerkowych w Beskidzie Żywieckim i Beskidzie Śląskim - Jaworski, Andrzej; Pach, Maciej (Leśne Prace Badawcze, 2014)
The aim of this research was to find out what changes occurred between 1999-2009 in Oszast reserve in the volume, species composition and diameter at breast height (dbh) distribution of the forest stand, and the number and height of regeneration. The objective was to determine what would be condition of these managed lower montane multispecies forest stands (Swiss irregular shelterwood method or selection cuttings) and what role spruce would play in them if they have not been replaced by spruce monocultures. The research was conducted on three permanent circular sample plots (s.p.), each had size of 1/3 ha. Over 10 years, standing volume of the forest stand increased on s.p. 1 (from around 562 m 3 ha -1 to 649 m 3 ha -1 ) and s.p. 3. (from 653 m 3 ha -1 to 660 m 3 ha -1 ), while decreased on s.p. 2. (from 421 m 3 ha -1 to 378 m 3 ha -1 ). The species composition, defined on the basis of volume share (averaged for the three s.p. jointly), did not undergo consistent changes. However, the relative dominance of beech over spruce was determined based on tree numbers. The average spruce mortality (averaged from three s.p.) did not exceed 10% and was slightly higher than that of beech (6%), and lower than fir mortality (15%). Nevertheless, spruce did not show any symptoms of dieback. The reasons behind its mortality were fallen trees and windbreaks. In regeneration, on the whole, beech or sycamore predominated, and the proportion of spruce and fir was small. In the future spruce and fir may even decrease further by competitive ability of dynamically regenerating beech. Abandonment of forest management to promote greater diversity of species, may favour the formation of beech monocultures, or forest stands dominated by beech, everywhere that beech is already present or will be introduced. The maintenance of stable, multispecies forest stands, with co-dominant fir, beech and spruce of native origin, requires natural or artificial regeneration of spruce and fir, manipulated to restore fir up to about 30%, and reduce spruce down to about 40%. This would be possible through the use of the Swiss irregular shelterwood method and selection system, and by continuous tending of regeneration.